The Effect of Eco-Friendly Packaging on Consumer Purchase Intention: a Study of Coca-Cola Sustainable Packaging Practices - Binti Azaini Imran, Nur Fatin Nabilah; Binti Noor Effendee, Nur Firyal; Binti Mohd Faris, Nur Hazwani Husna; Binti Mohd Puad, Nur Irdina Safi; Nitin, Nitin; Verma, Vanshika; Mayur, Kumar; Lim, Hui Ling; Ng, Wei Chien; Baliyan, Meenu; Kee, Daisy Mui Hung (Journal of The Community Development in Asia, 2024)
Being among the biggest beverage manufacturers in the world, Coca-Cola has recently embraced a variety of sustainability measures, such as water conservation, reduced packaging, and the use of renewable energy. However, the idea begs the issue of whether consumers have intention to purchase Coca-Cola if the product adopts greener practices. This study examines the effect of ecologically friendly packaging on Consumer purchase intention, use Coca-Cola as a case study. An online survey was utilized to gather primary data from 100 Coca-Cola customers in order to better comprehend and support the research findings. We investigated whether environmental concerns about awareness of brand and Coca-Cola sustainable packaging practices and awareness of eco-friendly influence will affect the purchase intention of consumers on Coca- Cola. This research provides fresh insights on consumers' perception of Eco-friendly packaging, and how this perception may encourage consumer purchasing decisions.